Perinatal injury of the central nervous system in Lithuania from 1997 to 2014 - Basys, Vytautas; Drazdienė, Nijolė; Vezbergienė, Nijolė; Isakova, Jelena (Acta medica Lituanica, 2017)
Background. Perinatal CNS injuries are significant for the health of neonates and for child development at a later period. The aim of this study was to evaluate the dynamics of the frequency of perinatal CNS lesions (corresponding to ICD 10 code P91) over a 20-year period, using the data collected from the Lithuanian Medical Data of Births (Registry of Births). Material and methods. In total, data of 559,164 newborns were analyzed. Results. During the period from 1997 to 2014, the frequency of term newborns with perinatal CNS injury decreased almost two times, from 20.4/1000 live births in 1997 to 15.5/1000 live births in 2014, or from 3.12% (95% CI 2.95; 3.31) to 1.46% (95% CI 1.32; 1.61). In 18 years, the rate of infant mortality from perinatal CNS injury decreased by more than four times and in 2014 it was 0.3/1000 births; it accounts for 11% of neonatal mortality (2.6/1000 live births). The largest decrease of CNS injury was seen after a caesarean birth (from 13.7% in 1999 to 1.7% in 2014) and breech delivery (from 9.7% in 1999 to 0.8% in 2014). Analysis of the dynamics of perinatal CNS injury in preterm births in selected groups did not identify a significant positive shift during the period. When evaluating the level of childbirth services in different-level maternity hospitals, CNS injury is undoubtedly diminished in 2B-level maternity hospitals (regional). Also, positive dynamics was observed in the data of 2A-level maternity hospitals, while in 3-level maternity hospitals (university hospitals), which deal with the most complicated obstetrical pathology and preterm newborns, positive dynamics was not observed. It is estimated that the frequency of hypoxic-ischemic encephalopathy was 0.63/1000 live births in Lithuania in 1993. Conclusions. The frequency of perinatal CNS injury and its positive dynamics in over 18 years shows a progressive and scientifically-based perinatal health care organization in Lithuania.